Development and validation of instrument for assessment of situational awareness in operational management of nursing leaders in hospital settings - von Gerich, Hanna; Junttila, Kristiina; Pasanen, Miko; Salanterä, Sanna; Peltonen, Laura-Maria (Finnish Journal of eHealth and eWelfare, 2023)
Nursing leaders in charge of operational management in acute care environments need continuous real-time information regarding workflow, human resources, and patient situations to support their immediate decision making. However, nursing leaders report that the current information systems do not provide sufficient support to help their decision making. The aim of this study was to develop an instrument for the evaluation of situational awareness of nursing leaders in operational management into the hospital setting. First, an established situational awareness scale was combined with literature to develop a draft for the instrument. Second, an expert panel assessed the content validity of the instrument, and finally, the psychometric properties of the instrument were evaluated by a cross-sectional online survey. The final version of the instrument consisted of three dimensions: Demands of patient care (5 items), Human resources (5 items) and Materials (6 items). The scale content validity index for all 16 items was 0.88. The instrument was tested with nursing professionals in charge of operational management (n=349). The overall situational awareness was 4.18, the highest dimension was the human resources (mean 4.63), while lowest score was seen for the dimension patient care (mean 3.84). The construct validity and internal consistency of the instrument was deemed good. The instrument may support systematic assessments of situational awareness, pinpointing areas of information management that need improvement. It may support evaluation of development projects, interventions, or implemented information systems. As situational awareness is an integral element of operational management in all health care, future research should explore it in other clinical environments and with other professions.